To Smoke or Not To Smoke: Cigarettes Have a Negative Effect on Wound Healing of Diabetic Foot Ulcers. (December 2018) - Álvaro-Afonso, Francisco Javier; Lázaro-Martínez, José Luis; Papanas, Nikolaos
Diabetic foot ulcers (DFUs) have a complex pathophysiology and require an expert multidisciplinary treatment. There are several, both systemic and local, risk factors for DFUs. A recent meta-analysis of 18 studies has now provided robust evidence on the detrimental effect of smoking on healing of DFUs. Indeed, healing rates were consistently lower among smokers than among nonsmokers. Based on this new evidence, it is reasonable to consider the utility of smoking cessation programs. Incorporation of the latter into the holistic therapeutic strategy for DFUs may be anticipated to improve healing rates, but this remains to be shown.